Is multi-level marketing of nutrition supplements a legal and an ethical practice?. (June 2018) - Cardenas, Diana; Fuchs-Tarlovsky, Vanessa
Summary: Background: Multi-level marketing (MLM) of nutrition products has experienced dramatic growth in recent decades. 'Wellness' is the second most popular niche in the MLM industry and represents 35% of sales among all the products in 2016. This category includes dietary supplements, weight management and sports nutrition products. The aim of this paper is to analyse whether this practice is legal and ethical. Methods: An analysis of available documentary information about the legal aspects of Multi-level marketing business was performed. Ethical reflexion was based on the "principlism" approach. Results: We argue that, while being a controversial business model, MLM is not fraudulent from a legal point of view. However, it is an unethical strategy obviating all the principles of beneficence, nonmaleficence and autonomy. What is at stake is the possible economic scam and the potential harm those products could cause due to unproven efficacy, exceeding daily nutrient requirements and potential toxicity. The sale of dietary and nutrition supplements products by physicians and dieticians presents a conflict of interests that can undermine the primary obligation of physicians to serve the interests of their patients before their own. Conclusion: While considering that MLM of dietary supplements and other nutrition products are a legal business strategy, we affirm that it is an unethical practice. MLM products that have nutritional value or promoted as remedies may be unnecessary and intended for conditions that are unsuitable for self-prescription as well.